Assessment of fish farming effects on aquatic systems in Assis and Candido Mota, Sao Paulo, by using a water quality index and multivariate statistical analysis - Simes, Fabiano dos Santos; Santos Yabe, Maria Josefa dos; Moreira, Altair B. [UNESP]; Bisinoti, Marcia Cristina [UNESP] (Soc Brasileira Quimica, 2007)
In this work, the impact of fish farming activities on the Queixada, Macuco and Pari-Veado Rivers in the Paranapanema watershed was evaluated. Physical, chemical and microbiological parameters were quantified in these aquatic systems followed by application of multivariate statistical analysis (MSA) and water quality index (WQI) tools. Watersheds where fish fanning activities are predominant presented WQI >= 52 indicating good quality, whereas MSA demonstrated bad quality for these aquatic bodies. The results showed that the degradation in this watershed follows the fish farming activity. The MSA index is more restricted than the National Foundation Sanitation (NFS) index routinely used to infer water quality.
Keywords: water quality index (WQI); multivariate statistical analysis; fish farming activities